Quantitative Comparison of Breast Cancer Resistance Protein (BCRP/ABCG2) Expression and Function Between Maternal Blood-Brain Barrier and Placental Barrier in Mice at Different Gestational Ages - Fujita, Arimi; Noguchi, Saki; Hamada, Rika; Shimada, Tsutomu; Katakura, Satomi; Maruyama, Tetsuo; Sai, Yoshimichi; Nishimura, Tomohiro; Tomi, Masatoshi (Frontiers in Drug Delivery, 2022)
Breast cancer resistance protein (BCRP) is expressed by brain capillary endothelial cells and at the interface between two placental syncytiotrophoblast layers in rodents, and serves to suppress drug distribution to the brain and the fetus. The purpose of the present study is to determine and compare the apparent impact of a single BCRP molecule on drug transfer between the maternal blood brain barrier and placental barrier in pregnant mice at different gestation ages. BCRP protein was quantified by liquid chromatography-tandem mass spectrometry. Genistein or dantrolene was continuously administered to pregnant Bcrp-/- or wild-type (WT) mice, and the brain-to-plasma concentration ratio in the mother (Kp,brain) and the fetal-to-maternal ratio of plasma concentrations (Kp,fp) were determined. At gestational day 15.5 (GD15.5), the protein amount of BCRP at the murine placental barrier was estimated to be approximately 3 times higher than at the maternal blood brain barrier, but the levels were approximately the same at GD17.5 due to the decline of placental BCRP expression during gestation. On the other hand, the values of Bcrp-/-/WT ratio of Kp,brain for genistein and dantrolene were 6.1 and 3.8, respectively, while the Kp,fp ratios were all less than 2.0. These results indicate that the apparent impact of a single placental BCRP molecule on the restriction of drug distribution is much less than that of a single brain BCRP molecule, probably because the function of placental BCRP is attenuated by bypass transfer through the connexin26 gap junctions between adjacent syncytiotrophoblast layers. The present study also found that the expression amount of BCRP protein at the human placental barrier formed by the monolayer of syncytiotrophoblasts was lower than that in mice, but this species difference appears to be functionally compensated by the murine-specific bypass route through gap junctions, at least in part.